The Main Tasks Of Farms And Dekhkan Farms In Ensuring Productive Security In Uzbekistan - Samiyeva, Gulnoza Tokhirovna (The journal of contemporary issues in business and government, 2021)
This article talks about ensuring food security and what an important role farmers and dekhkan farms plays its. The problem of food security is exacerbated by the narrowing of the gap between the possibilities of agricultural production to meet the standards of human health per capita, and therefore it is necessary to study ways to solve the provision of food for humanity.